(untitled) (JOURNAL OF SOFTWARE ENGINEERING TOOLS & TECHNOLOGY TRENDS, 2022)
Arduino is a free and open-source computer hardware and software company for creating electronic projects. Arduino consists of a physical programmable circuit board which is also known as a microcontroller and a software known as an IDE (Integrated Development Environment). It develops and sells microcontroller kits for the construction of digital devices. Computer code can be written and uploaded to the physical board with its use and it runs on your computer. This project uses an Arduino Uno board with a microcontroller, servo motor, and ultrasonic sensor to create a smart dustbin. The top of the dustbin has an ultrasonic sensor that measures the dustbin’s Stature. The project’s hardware and software are open-source and licenced under the LGPL & GNU. Preassembled Arduino boards or do it yourself kit are commercially available. Its design incorporates or include a number of microprocessors and controllers. The boards has a variety of digital and analogue input/output (I/O) pins that can be used to connect various expansion boards (shields) and other circuits. The Arudino board are also used to load programmes from personal computers.